PCASSO: A fast and efficient Cα‐based method for accurately assigning protein secondary structure elements. Issue 24 (4th July 2014) - Law, Sean M.; Frank, Aaron T.; Brooks, Charles L.
Abstract : Proteins are often characterized in terms of their primary, secondary, tertiary, and quaternary structure. Algorithms such as define secondary structure of proteins (DSSP) can automatically assign protein secondary structure based on the backbone hydrogen‐bonding pattern. However, the assignment of secondary structure elements (SSEs) becomes a challenge when only the Cα coordinates are available. In this work, we present protein C‐alpha secondary structure output (PCASSO), a fast and accurate program for assigning protein SSEs using only the Cα positions. PCASSO achieves ∼95% accuracy with respect to DSSP and takes ∼0.1 s using a single processor to analyze a 1000 residue system with multiple chains. Our approach was compared with current state‐of‐the‐art Cα‐based methods and was found to outperform all of them in both speed and accuracy. A practical application is also presented and discussed. © 2014 Wiley Periodicals, Inc. Abstract : Protein secondary structure elements (SSEs) are typically assigned based on backbone hydrogen‐bonding patterns. However, when it comes to assigning SSEs using only the Cα positions, the current state‐of‐the‐art is lacking in both accuracy and speed. To this end, protein C‐alpha secondary structure output (PCASSO) is presented–a fast and accurate Cα‐based SSE assignment tool that can be used for universal SSE assignments, high‐throughput SSE studies, analysis of coarse‐grained simulations, and so forth.